On meta-metaphysical nihilism—inexpressibility of denying the world - Chua, Joshua Jian Bin (Nanyang Technological University, 2024)
Meta-metaphysical nihilism is the view that metaphysics, the study of the nature of reality as reality, is impossible. One famous proponent of this view is Markus Gabriel, who argues for meta-metaphysical nihilism based on the claim that the World, or the totality of reality, does not exist. Briefly, Gabriel argues that because existence is manifold, reality is plural, not monistic. This plurality blocks any attempt to characterize the nature of reality, which blocks any attempt to substantively unify absolutely everything in reality. In response, James Hill argues that Gabriel’s view cannot be expressed without performative contradiction, as Gabriel’s claim that the World does not exist requires the use of the unrestricted quantifier for its expression. In this essay, I propose a reply that Gabriel could give to Hill’s Inexpressibility Objection. I argue that Gabriel’s No World View ought to be taken as a structural claim, not a conceptual, or substantive one, and propose a way to express the structural claim ‘the World does not exist’ without performative contradiction. To do this, I suggest that Gabriel give up his commitment to block the unrestricted quantifier, and instead allow for restricted uses of the unrestricted quantifier to make structural claims about existence.